PENGARUH PENILAIAN KINERJA DAN MOTIVASI TERHADAP PRODUKTIVITAS PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH DAN PENGEMBANGAN SUMBER DAYA MANUSIA KEBUPATEN KEPAHIANG - Ermy Wijaya; Pipin Permata Sari (Universitas Prof. Dr. Hazairin SH, 2020)
The purpose of this study is to find out the effect of performance assessment and motivation on employee productivity in the Regional Personnel and the Human Resources Development of Kepahiang Regency. This type of research is quantitative research and causal research, because it proves the causal correlation influenced by the variables studied. Respondents in this study were civil servants from the Regional Personnel and the Human Resources Development of Kepahiang Regency, the samples were 32 people. Data collection techniques using questionnaires and the data obtained were analyzed using SPSS with partial correlation test, multiple regression test, statistical test (t test and f test).The results showed that from the ttest obtained tcount for the performance appraisal variable the motivational variable which means that there is a partial effect of performance appraisal (X1) and motivation (X2) on the productivity (Y) of employees at the Regional Personnel Agency and the Human Resources Development of Kepahiang Regency. Based on the results of statistical tests, the calculated with a which means that there is an effect the effect of performance assessment and motivation on employee productivity in the Regional Personnel and the Human Resources Development of Kepahiang Regency. Value or This means that the contribution of the Performance Assessment (X1) and Motivation (X2) variables in influencing Employee Productivity (Y) is influenced by other variables not examined in this study.